O19.6 Use of Surfactant Vesicles as a Potential Gonococcal Vaccine Delivery System to Generate Antibody Against Neisserial Lipooligosaccharide. (13th July 2013) - Stein, D; Zimmerman, L; Park, J; Stocker, L; DeShong, P
Abstract : Background: To date, no one has been able to exploit the immunological potential of neisserial lipooligosaccharide (LOS) as a vaccine candidate. Methods: We have developed a glycoconjugate vaccine (TRIAD) that contains native LOS derived from Neisseria gonorrhoeae F62)ΔlgtD (a strain that produces lacto-N-neotetraose LOS and a peptide (PADRE) that possesses the ability to bind to a large number of HLA class II molecules, inserted into a surfactant vesicle. TRIAD is a catanionic surfactant vesicle formulation and the resulting vesicle is stable at room temperature for years, unlike a typical liposome. TRIAD is so robust that it can be autoclaved without any appreciable loss of structural integrity. Results: Using TRIAD that contained LOS and PADRE at a ratio of 10:1, and immunising with 2 μg of LOS equivalent, we were able to demonstrate that our vaccine induces a high titer anti-LOS antibody response, with the majority of the elicited antibody being IgG. Intraperitoneal immunisation of mice with our vaccine construct produced no observable adverse effects in mice, while intraperitoneal immunisation with equivalent amounts of purified LOS induced significant adverse effects. Conclusions: Our surfactant vesicle platform possesses all of the advantages seen with traditional liposome formulations, without any of the inherent problems associated with liposome-mediated vaccines. This vaccine platform readily lends itself to further modifications in that it is possible to include additional neisserial proteins into the vaccine via a novel whole cell extraction protocol. We believe that this will allow us to generate a universal vaccine able to protect against all serotypes of N. meningitidis.